Time-Varying Consensus Control Method of Hybrid Hierarchical Distributed Formation - Hongyun Wang; Min Gao; Dan Fang; Whenzhao Li; Zihua Kong (International Journal of Aerospace Engineering)
Aiming at the problem of formation control, a hybrid hierarchical distributed formation structure based on the virtual leader, centralized, and distributed structure is proposed and named active agent AA. Based on the established formation structure, a time-varying formation consensus control model and the changed model with no collision condition, which combined the formation flight problem with the collision avoidance problem are constructed, simplified the structure of the controller, then theoretically analyzed the consensus conditions of non-AA agents, and AA agent, respectively, obtained the necessary conditions of consistent convergence, and finally, simulated a formation with one virtual leader and four followers; the simulation results show that the control law designed in this study achieved the velocity consensus of non-AA agents and the location consensus of the AA agent; it also shows that the hybrid hierarchical distributed formation structure proposed in this study is reasonable, effective, and achievable.